Harvestmen (Arachnida: Opiliones) of the protected areas of the province of Buenos Aires and the Autonomous City of Buenos Aires, Argentina - Guerrero, Elián Leandro (2019)
The province of Buenos Aires plus Autonomous City of Buenos Aires, Argentina,house a varied range of physiognomies, from gallery forests in its northern sector to xerophilous scrubs in the south. The objective of this work is to compile a list of harvestmen species from all the protected areas of which information is available within that territory. Records of 17 species in 30 protected areas were obtained. Most of the areas with harvestmen records are located in the northeast of the province; there are few protected areas in the center and south, and there are not protected areas in western Buenos Aires. Some areas of great importance for the conservation of biodiversity (e.g ., natural reserves in San Nicolás, Zárate, Cañuelas, Azul, Tornquist, San Cayetano, Coronel Dorrego, etc.) have not yet been prospected to know their harvestmen composition. According to the zoogeographic scheme based on order Opiliones, most of the protected areas have Mesopotamian fauna, Pampean fauna, or both, and the Central fauna is poorly protected.